Analysis of Import and Export Activities in the Oil and Gas and Non-Oil and Gas Sectors and Their Impact on the Trade Balance in Foreign Trade in 2021 – 2024 - Wiwit Rohaeni Yulianti; Athiy Dina Rosihana (CV Edujavare Publishing, 2026)
Foreign trade plays a crucial role in accelerating Indonesia's economic growth after the pandemic. The purpose of this study is to examine trends in the development of export and import values in the oil and gas (O&G) and non- oil and gas (Non-O&G) industries from 2021 to 2024. Furthermore, this study attempts to identify factors causing changes in the trade balance. Quantitative descriptive research was conducted using secondary data from the Central Statistics Agency (BPS) periodic reports. Data analysis shows that the oil and gas industry has experienced a chronic deficit annually. This is due to a decline in domestic crude oil production capacity and a high dependence on fuel imports. In 2022, the largest oil and gas deficit reached US24,419.1 million, caused by the surge in global energy prices. Conversely, the non-oil and gas sector saved the economy by posting a massive surplus. The phenomenon of soaring commodity prices for coal and palm oil in 2022 peaked at US78,670.4 million. The strong performance of non-oil and gas exports has proven capable of covering the oil and gas sector deficit, so Indonesia's overall trade balance remains in the positive zone.